Effects of Collective Bargaining on Industrial Disputes Management - Egesa Simon Ukokhe; Olouch Mercy Florah (European Scientific Journal, ESJ, 2022)
Industrial conflict appears to be a major problem hindering development in developing countries in general. It has been established that industrial disputes cause economic losses to organizations and poor relationship among employees and employers. Although conflict in an organization is inevitable, it should be understood that disputes between employees and employers must be reduced through mutually agreed mechanisms to a reasonable level that enable creativity and performance of employees and the organization at large. This paper focuses on reviewing the effect of collective bargaining on industrial disputes management. The existing literature on collective bargaining, joint consultation, grievance handling, and industrial dispute management was also examined. The study objectives further establish how collective bargaining, joint consultation, and grievance handling mechanism influence dispute management in an organization.  Pluralism theory and human relations theory was used as a guide for this study. It was concluded that collective bargaining agreement, joint consultation, and grievance handling are key tenets of industrial dispute management. All parties are recommended to respect the rights of each party in negotiation and the agreement reached should be documented and cited as the point of reference in resolving disputes. The management should strive to allow a give and take position while resolving conflicts, provide grievance handling process that is timely, fair, involve both parties, and ensure that grievance capturing mechanism is readily available to all parties. Joint consultation committees, union, and management should also coexist to resolve any dispute which arises. In mutual coexistence environment, the organization is able to tap into the stock of ideas, which are available within the organisation.